The effects of inducing a follicular phase gonadotropin secretory pattern in normal women during the luteal phase - Bremner, William J.; Clifton, Donald K.; Soules, Michael R.; Steiner, Robert A. (Elsevier, 1987)
It has been hypothesized that the slowing of the luteinizing hormone (LH) pulse frequency in the luteal phase may be necessary for the demise of the corpus luteum, the intercycle rise in baseline follicle-stimulating hormone (FSH), or ovarian follicular development in the subsequent cycle. For assessment of the physiologic role of the luteal phase LH pulse pattern, this pattern was converted to a follicular pattern in six normal women who used exogenous gonadotropin-releasing hormone administered with a portable pump (dose 50 to 100 ng/kg subcutaneously every 90 minutes beginning in the early luteal [n = 3] and midluteal [n = 3] cycle phases). There was no significant difference between the treated and the subsequent cycle for luteal progesterone production [186.3 versus 159.0 (ng/ml) day], preovulatory follicular size (23.1 versus 22.5 mm), estradiol levels, luteal phase length (15.6 versus 14.3 days), and daily gonadotropin concentrations including the intercycle FSH rise (160.5 versus 139.1 ng/ml). A follicular phase gonadotropin pulse pattern (increased frequency, decreased amplitude) in the luteal phase had no discernible effects on the corpus luteum or on follicular development in the subsequent cycle.
Keywords: male contraception; andrology; 5-alpha reductase inhibitors; testosterone; gonadotropins; colchicine; klinefelter's syndrome; reifenstein's syndrome; spermatogenesis; Humans; Follicular Phase; Luteinizing Hormone, blood; Research Support, U.S. Gov't, P.H.S.; Luteal Phase; Pituitary Hormone-Releasing Hormones, pharmacology; Female; Follicle Stimulating Hormone, blood; Adult